Z = -b - a + 1
subtract 1
1z - 1 = -1b - 1a ( 1z is the same as z, same goes for b and a)
add -1b
1b - 1z - 1 = -1a
then we remove -1 by dividing it.
-1b -(-1z) + 1
Answer: -1b -(-1z) + 1 = A
A negative minus a negative is a positive, so the answer might as well be....
-1b + 1z + 1 = A
Answer:
10/99
Step-by-step explanation:
40/396
40÷4/396÷4
10/99
First, determine the circumference (C) of the circle, the equation,
C = 2πr
Substituting the value or the radius,
C = 2π ( 4) = 8π
The arc length is the product of the circumference and the ratio between the subtended angle and 360. The mathematical expression is already,
S = (8π) x (72 / 360) = 0.8π
Thus, the arc is 0.80π.
Answer:
3/2
Step-by-step explanation:
(3/4)/(1/2)=(3/4)(2/1)=6/4=3/2